Essays on Gödel’s Reception of Leibniz, Husserl, and Brouwer - van Atten, Mark (Springer, 2015)
This volume tackles Gödel's two-stage project of first using Husserl's transcendental phenomenology to reconstruct and develop Leibniz' monadology, and then founding classical mathematics on the metaphysics thus obtained. The author analyses the historical and systematic aspects of that project, and then evaluates it, with an emphasis on the second stage.